2020
DOI: 10.30598/a.v8i2.1009
|View full text |Cite
|
Sign up to set email alerts
|

Isolasi, Seleksi, dan Uji Antagonis Bakteri Endofit diisolasi dari Salawaku (Falcataria mollucana) dalam Menekan Pertumbuhan Cendawan Patogen Cercospora spp

Abstract: Penelitian bertujuan untuk mendapatkan isolat bakteri endofit dari akar, daun dan batang Salawaku (Falcataria mollucana) dan menguji kemampuan antagonis bakteri tersebut dalam menekan pertumbuhan cendawan patogen Cercospora spp penyebab penyakit bercak merah pada tanaman Samama (Anthocephalus macrophyllus).Isolasi dilakuka dari dua tanaman sampel yang tumbuh di dua lokasi yang berbeda ketinggian tempat yaitu di Kampus Fakultas Pertanian Unpatti dan Kampus IAIN Ambon. Sebanyak 10  isolat dan 7 isolat diperoleh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
2
1
2
Order By: Relevance
“…According to the results obtained, the endophytic bacterial isolates from the nutmeg plant showed the highest total population in the seeds at 7.5x10 4 CFU/ml, followed by fruit flesh of 3.0x10 4 CFU/ml, stems of 2.8x10 4 CFU/ml, leaves of 4.6x10 3 CFU/ml, and leaf bones of 4.1x10 3 CFU/ml. In contrast to results obtained by Marsaoli et al, (2019) which reported that the population of endophytic bacteria from plant stem tissue is usually higher than that of other organs such as flowers, fruits and seeds. However, it is still possible that the total population of endophytic bacteria in other organs is more than in the stem.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…According to the results obtained, the endophytic bacterial isolates from the nutmeg plant showed the highest total population in the seeds at 7.5x10 4 CFU/ml, followed by fruit flesh of 3.0x10 4 CFU/ml, stems of 2.8x10 4 CFU/ml, leaves of 4.6x10 3 CFU/ml, and leaf bones of 4.1x10 3 CFU/ml. In contrast to results obtained by Marsaoli et al, (2019) which reported that the population of endophytic bacteria from plant stem tissue is usually higher than that of other organs such as flowers, fruits and seeds. However, it is still possible that the total population of endophytic bacteria in other organs is more than in the stem.…”
Section: Discussioncontrasting
confidence: 96%
“…Interestingly, each endophytic bacterial strain has its own ability to determine its habitat, thus the total population of endophytic bacteria in each plant organ is different. This depends on the type of plant, plant species, plant age, plant genotype, plant tissue type, research methods and techniques used, geographical conditions of the environment, surface sterilization process, and culture medium used (Marsaoli et al, 2019) According to the results of this study, the number of endophytic bacterial isolates obtained from the nutmeg plant (Myristica fragrans Houtt) was 10 isolates with the composition: 2 isolates from seeds, 2 isolates from leaves, 2 isolates from leaf bones, and 2 isolates from meat. fruit.…”
Section: Discussionmentioning
confidence: 99%
“…The secondary metabolite resulting from the bacteria extract B. cereus 11uj can inhibit the growth of mushrooms R. solani and P. oryzae which is good enough at concentrations of 1,000 ppm, and the antifungal activity produced more effectively inhibits the growth of P. oryzae (Suryadi et al, 2015). One mechanism of emphasis by the endophytic bacteria in the genus Bacillus is antibiosis, through the generation of a bulbiformin antibiotic that is toxic to various plant pathogens (Marsaoli et al, 2019). Bacterial isolates are potential as biofertilizers that produce enzymes; bacteria as a source of enzymes are more beneficial because of their rapid growth.…”
Section: Discussionmentioning
confidence: 99%
“…Kemampuan endofit dalam menunjukan bahwa bakteri endofit mampu menghambat cendawan Pestalotipsis sp. melalui produksi senyawa antimikrob, meka-nisme kerja bakteri endofit dalam pengendalian hayati meliputi : mengeluarkan antimikroba, kompetisi ruang dan nutrisi (Marsaoli et al, 2020). Beberapa bakteri didapatkan bertindak sebagai agen hayati yang berasosiasi dengan tanaman ianangnya, dalam penelitian ini isolat bakteri endofit terpilih menunjukkan antibiosis terhadap Pestalotiopsis sp., mekanisme antibiosis berkaitan erat dengan kemampuan isolat bakteri endofit menghasilkan enzim seperti kitinase, protease,dan selulase maupun senyawa sekunder lainnya yang sangat berperan dalam degradasi dinding sel cendawan patogen (Hallmann et al, 1997).…”
Section: Persentase Daya Hambat Miselium Cendawan Pestalotiopsis Sp O...unclassified
“…Pada bakteri gram negatif, dinding sel hanya setebal 1-3 lapis, di hadapan kalium hidroksida, dinding sel gram negatif mudah terganggu, melepaskan bahan kromosom viskid, yang menyebabkan suspensi bakteri menjadi tebal dan berserat. Dinding sel bakteri gram positif tidak terpengaruh oleh 3% KOH (Madigan et al, 2012;Kurnia et al, 2015).…”
Section: Reaksi Gram Dengan Menggunakan Metode Koh 3% Dan Metode Perw...unclassified